Irreversibility of Pressure Induced Boron Speciation Change in Glass - Smedskjaer, Morten M. (Nature Publishing Group, 2014)
It is known that the coordination number (CN) of atoms or ions in many materials increases through application of sufficiently high pressure. This also applies to glassy materials. In boron-containing glasses, trigonal BO(3) units can be transformed into tetrahedral BO(4) under pressure. However, one of the key questions is whether the pressure-quenched CN change in glass is reversible upon annealing below the ambient glass transition temperature (T(g)). Here we address this issue by performing (11)B NMR measurements on a soda lime borate glass that has been pressure-quenched at ~0.6 GPa near T(g). The results show a remarkable phenomenon, i.e., upon annealing at 0.9T(g) the pressure-induced change in CN remains unchanged, while the pressurised values of macroscopic properties such as density, refractive index, and hardness are relaxing. This suggests that the pressure-induced changes in macroscopic properties of soda lime borate glasses compressed up to ~0.6 GPa are not attributed to changes in the short-range order in the glass, but rather to changes in overall atomic packing density and medium-range structures.